LITERASI PROFESI WARTAWAN PADA GURU DAN TENAGA PENDIDIK DI CIMAHI - Nurdin, Iman Soleh; Lusiawati, Ira; Solihin (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2026)
The current era of information disruption presents significant challenges for educational institutions in Cimahi City, particularly in distinguishing professional journalists from fraudulent or “bodrex” journalists who misuse the profession. Limited journalism literacy often leads to negative stigma and excessive caution among schools when dealing with the media. This Community Service Program (PkM) aims to enhance teachers’ and education personnel’s understanding of the journalism profession, enabling them to respond critically while fostering constructive media relations.The method employed involved interactive socialization and educational sessions on Press Law No. 40 of 1999, the Journalistic Code of Ethics, and Journalist Competency Standards. The activity was conducted on December 13, 2025, involving 80 participants from elementary and junior high schools in Cimahi City. The results indicate an increased understanding of the strategic role of school public relations as a gatekeeper, the mechanism of the right of reply, and legal protection against intimidation. This improved literacy encourages a paradigm shift toward more professional and collaborative media partnerships.